Active Gas Thrust Bearing With Embedded Digital Valves and Backpressure Sensors. Issue 5 (3rd September 2017) - Colombo, Federico; Maffiodo, Daniela; Raparelli, Terenziano
ABSTRACT: The present article describes a low-cost active aerostatic thrust bearing controlled via an Arduino card and with feedback transducers and valves embedded in it. Efforts were made to design a compact thrust bearing with small overall dimensions, robust behavior, and reduced costs. Two embedded electropneumatic digital valves are controlled with pulse width modulation (PWM) logic and used to modify the thrust bearing supply pressure. The feedback signal for the control comes from two embedded backpressure sensors designed and characterized for this purpose. The test benches required for static and dynamic thrust bearing characterization are described; preliminary experimental tests were carried out in open and closed loop configurations. The closed loop configuration of the system, with a proportional integral (PI) control, shows good behavior and the time needed for the thrust bearing to return to the reference gap value after a force perturbation of 40 N is about 0.1 s.